2007
DOI: 10.1007/s11227-007-0128-2
|View full text |Cite
|
Sign up to set email alerts
|

Perfect load balancing on the star interconnection network

Abstract: In this paper, we use the regular distribution method to design a perfect load balancing algorithm for an n-star with a maximum error of 1 and a time complexity of 3n(n + 1). This algorithm is based on the novel notion of leader trees. A second algorithm proposed in this paper as an enhancement to our first algorithm and uses an arbitrary spanning tree as the leader tree and has a worst time complexity of 2.25n 2 − 3n + 0.75. We also discuss the issue of dynamically selecting the leader tree and hybrid load ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Furthermore the reached outcome and the issued results of the simulation from Zaho et al of the proposed algorithms on load balancing has shown a considerably big improvements in enhancement in redistribution the load balancing of the processors of the topology [12]. In a different literature and research done by Zaho and Xiao they investigated a different algorithm named t DED-X for load balancing on homogeneous optoelectronic technology and they proposed new algorithm framework, Generalized Diffusion-Exchange-Diffusion Method, this framework was efficient for the load balancing distribution on the Heterogeneous optoelectronic technology [11,13,14].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Furthermore the reached outcome and the issued results of the simulation from Zaho et al of the proposed algorithms on load balancing has shown a considerably big improvements in enhancement in redistribution the load balancing of the processors of the topology [12]. In a different literature and research done by Zaho and Xiao they investigated a different algorithm named t DED-X for load balancing on homogeneous optoelectronic technology and they proposed new algorithm framework, Generalized Diffusion-Exchange-Diffusion Method, this framework was efficient for the load balancing distribution on the Heterogeneous optoelectronic technology [11,13,14].…”
Section: Background and Related Workmentioning
confidence: 99%
“…In the framework designing of server group, based on the user's habits, we can reduce the pressure of a single database by partition more particularity and make the server gives the appropriate supports to varying partition. Also, using complex strategies to adjust the distribution of user's login, improving the configuration of the system to achieve the expansion of system capacity by simply stacking to suitable with the increasing users are what should we pay enough attention to [21][22][23][24].…”
Section: Prospectsmentioning
confidence: 99%
“…An interconnection network can be modeled by a graph where a processor is represented by a node, and a communication channel between two processing nodes is represented by an edge between corresponding nodes [1,4,24]. Various topologies for interconnection networks have been proposed in the literature; these include cubic networks (e.g., meshes, tori, k-ary n-cubes, hypercubes, folded cubes, and hypermeshes), hierarchical networks (e.g., pyramids and trees), and recursive networks (e.g., RTCC networks, OTIS or swapped networks, WKrecursive networks, and star graphs) that have been widely studied in the literature for their topological properties [5,[8][9][10][11][12][13]15,18,19,26,27], communication algorithms [3,7,10,11,13,19,21,22,26,29] and popular applications [4,24,14,16,32], embedding capabilities [6,9,23,25,28,29] and reliability and fault-tolerance issues [2,3,7,9,17,20,28,30,…”
Section: Introductionmentioning
confidence: 99%